1995
DOI: 10.1104/pp.109.4.1141
|View full text |Cite
|
Sign up to set email alerts
|

Phytochelatins and Related Peptides (Structure, Biosynthesis, and Function)

Abstract: Plants obtain micronutrients such as Cu and Zn from aquatic and terrestrial environments that may also provide the metals Cd, Pb, and Hg. These essential and nonessentia1 metals exist at low to high concentrations depending on natural and manmade disturbances. In a fluctuating environment the plants may experience shifting internal concentrations of these bioreactive metals. Therefore, it is beneficial for plants to have mechanisms that (a) maintain internal concentrations of essential metals between deficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
283
0
11

Year Published

1997
1997
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 647 publications
(299 citation statements)
references
References 34 publications
5
283
0
11
Order By: Relevance
“…With cadmium modulating the splicing decision to give the "correct" product for detoxification of heavy metals, Bz2 would thus be considered a metal-activated protein. Cadmium can also regulate enzymes posttranslationally; PC synthase is activated directly by cadmium (Rauser, 1995). In summary, the maize Bz2 gene and other type 111 plant GSTs may encode multifunctional stress proteins.…”
Section: Sc Ussl Onmentioning
confidence: 99%
“…With cadmium modulating the splicing decision to give the "correct" product for detoxification of heavy metals, Bz2 would thus be considered a metal-activated protein. Cadmium can also regulate enzymes posttranslationally; PC synthase is activated directly by cadmium (Rauser, 1995). In summary, the maize Bz2 gene and other type 111 plant GSTs may encode multifunctional stress proteins.…”
Section: Sc Ussl Onmentioning
confidence: 99%
“…In plants heavy metal tolerance and hyperaccumulation are thought to be the result of complexation and sequestration of heavy metal ions by specific cysteine-rich polypeptides, known as metallothioneins (MTs) and phytochelatins (PCs), respectively [1,2]. While MTs are gene products, PCs are synthesized enzymatically from glutathione (or related pep tides).…”
Section: Introductionmentioning
confidence: 99%
“…Due to its intracellular abundance, GSH is a likely target for metal cations, especially those having high affinity for thiolate sulfur [3]. It has been suggested that GSH may serve as a primary defense against metal cation toxicity [4,5]. Reduced glutathione (GSH), present in nuclei at concentrations ranging from 1 and 10 mM, has been implied as a protective agent against heavy metal cation toxicity through forming complexes [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%